ISOLATION AND IDENTIFICATION OF BRUCELLA SUIS IN PIGS AS ZOONOTIC DISEASE IN ENDEMIC AREAS OF EAST JAVA, INDONESIA - Koestanti, Emy S; Misaco, Wiwik; Chusniati, Sri; Maslachah, Lilik (African Journal of Infectious Diseases (AJID), 2018)
Background: Brucellosis in pigs at East Java Indonesia has not only cause great economic losses due to a decrease in productivity of livestock but also are zoonotic. Infection on free brucelosis pigs were initially begun with the infected pigs both male and female, or the use of superior male pigs together. The elimination of the disease either on a group or population is considered as the most effective way to prevent the spread of the disease in pigs. Prevention efforts mainly addressed to vaccination, sanitary maintenace and government policy. The purpose of this study was to isolated and identified Brucella suis as the causative agent.Material and Methods: The survey area were the pig farm owned by breeder farmers in the area of East Java Indonesia, at Kediri, Malang, Blitar and Probolinggo district. Blood samples obtained were tested with RBT. Pigs are suspected of being infected with Brucella if the RBT was positive that characterized with agglutination in the test results. If RBT was positive, bacteriological examination will be performed, with samples of visceral foetus organ, ie liver, spleen, placenta and amniotic fluid. Isolation and identification of Brucella suis were used Brucella Broth and Brucella Agar, and if the bacteri growthwill be continued with biochemical test ie H2S, urease, citrate, catalase and oxidase test. The positive results of Brucella suis showed positive urease, catalase andoxidase,but negative for citrate and H2S. Results: RBT and bacteriolgical examination showed that 1 sample was positive Brucella suis, and 19 negative. The positive results showed positive urease, catalase and oxidase,but negative for citrate and H2S Conclusion: Based on RBT test and bacteriological examination, there was 1 positive sample of brucellla suis, that is sample coming from Kediri district.